Sosialisasi Pengelolaan Sampah Organik Dan Non Organik Menjadi Nilai Tambah Di SMPN 16 Kota Bengkulu Kelurahan Betungan - Sasmita, Erika Nanda; Harni, Suli; Puspita, Triana; Rahmandani, Lutviana; Agnesia, Dinda Dwi; Nur’aini, Hesti; Fariadi, Herri; Herlin, Herlin (LPPM Universitas Dehasen Bengkulu, 2025)
The increasingly complex waste problem in Indonesia requires an increase in public awareness, especially the younger generation, in managing waste from an early age. This activity aims to increase junior high school students' understanding of organic and non-organic waste management through interactive and educational socialization. The method used is a qualitative descriptive approach involving 21 participants, consisting of students and accompanying teachers at SMP Negeri 16 Bengkulu City. Data were collected through observation, short interviews, and documentation of activities. The results of the activity showed that students were enthusiastic about participating in the socialization and showed an increase in understanding of the types of waste and how to manage it, especially through the 4R method (Reduce, Reuse, Recycle, Recovery). The use of visual media and active discussions proved effective in increasing participant interest and involvement. The conclusion of this activity is that socialization is able to raise students' awareness of the importance of sorting and processing waste, and encourage them to become agents of change in maintaining the cleanliness of the school environment and its surroundings.